Proinflammatory Cytokine Expression in Apical Periodontitis from Diabetic Patients - Estéfano Borgo Sarmento; Rosana Helena Teixeira de Lima Ribeiro Andrade; Cinthya Cristina Gomes; Fábio Ramôa Pires; Maria Isabel Bastos Valente; Adalgiza Mafra Moreno; Marco Orsini; Dennis Carvalho Ferreira; Lucio Souza Gonçalves; Luciana Armada (International Journal of Dentistry)
Diabetes mellitus has been regarded as a condition capable of influencing the evolution of periapical lesions. Therefore, this study evaluated the immunoexpression of IL-1β, TNF-α, and IL-17 in apical periodontitis from type 2 diabetic patients through immunohistochemistry. Twenty-six periapical lesions were selected, and the images obtained through immunohistochemistry reactions were analyzed. The statistical significance was set at p<0.05. IL-1β expression was considered focal (54%), weak to moderate (38%), and strong (8%) in diabetics, and focal (46%), weak to moderate (31%), and strong (23%), in controls. TNF-α was focal (85%) and weak to moderate (15%) in diabetics, and focal (92%) and weak to moderate (8%), in controls. IL-17 was focal (8%), weak to moderate (46%), and strong (46%) in diabetics, and focal (62%), weak to moderate (8%), and strong (30%), in controls. The quantitative analysis revealed greater expression of IL-17, with a significant difference between IL-17 × IL-1β × TNF-αp=0.0009 in the diabetic group. The cytokines IL-1β and TNF-α did not express statistical differences between the tested groups. The IL-17 showed higher immunoexpression in the diabetic group p=0.047, which may suggest higher bone resorption activity in chronic apical periodontitis in this group of patients.